Evaluasi Kinerja Guru: Model dan Metode dalam Meningkatkan Mutu Pendidikan - Ilham Kamaruddin; Mike Nurmalia Sari; Abdurrahman Abdurrahman; Istiqomah Istiqomah; Herman Herman; Nining Andriani (Departement of Mathematics Education, 2024)
This article discusses the importance of a teacher performance evaluation approach oriented towards professional development in enhancing the quality of education. With a focus on aspects such as constructive feedback, transparency, and teacher involvement, this approach serves not only as an assessment tool but also as a means to foster continuous growth and improvement. The discussion encompasses key aspects such as support and resources, recognition of achievements, and the positive impact on student learning experiences. Empowering teachers through active participation in the evaluation process and support for their professional development not only influences individual performance quality but also contributes to school stability. Despite implementation challenges, this approach is recognized as an investment in shaping a better future for education.